Studi Karakteristik dan Pemilihan Rute Pengguna Jalan Tol Surabaya - Mojokerto terhadap Jalan Tol Krian-Legundi-Bunder-Manyar Menggunakan Metode Stated Preference - Agustina, Yanida; Widyastuti, Hera (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2020)
Krian-Legundi-Bunder-Manyar Toll Road is a part of the Non Trans Java Toll Road which is included in the national strategic project. Krian-Legundi-Bunder-Manyar Toll Road was built to facilitate the public and economic activities of Sidoarjo Regency (Krian), Gresik Regency and surrounding areas citizen. With Krian-Legundi-Bunder-Manyar Toll Road, the choice of routes connecting the Sidoarjo Regency (Krian) and Gresik Regency will increase. And each route choice has its own characteristics. For this reason it is necessary to analyze the route selection using stated preference method. Data collection of characteristics and route selection will be carried out by conducting a survey of toll road users at several points by interviewing them based on stated preferences method. To analyze the data, descriptive statistical theory and binomial logit regression will be used.